Covalent attachment of [Ni(alkynyl-cyclam)]2+ catalysts to glassy carbon electrodes. Issue 33 (5th April 2018) - Zhanaidarova, Almagul; Moore, Curtis E.; Gembicky, Milan; Kubiak, Clifford P.
Abstract : Surface modification of glassy carbon electrodes (GCEs) with molecular electrocatalysts is an important step towards developing more efficient heterogeneous CO2 reduction materials. Abstract : Surface modification of glassy carbon electrodes (GCEs) with molecular electrocatalysts is an important step towards developing more efficient heterogeneous CO2 reduction materials. Here, we report direct anodic electrografting of [Ni(alkynyl-cyclam)] 2+ catalysts to the surface of GCEs in one simple step using inexpensive earth-abundant chemicals. When modified, these electrodes show reversible electrochemistry in organic solvents with zero peak-to-peak separations (Δ E = 0) and non-diffusive I ( V ) profiles that are typical for heterogeneous redox materials. CPE of these electrodes showed enhanced formation of H2 gas relative to CO compared to homogeneous catalysts.